Electroceuticals for peripheral nerve regeneration. (1st October 2022) - Maeng, Woo-Youl; Tseng, Wan-Ling; Li, Song; Koo, Jahyun; Hsueh, Yuan-Yu
Abstract: Electroceuticals provide promising opportunities for peripheral nerve regeneration, in terms of modulating the extensive endogenous tissue repair mechanisms between neural cell body, axons and target muscles. However, great challenges remain to deliver effective and controllable electroceuticals via bioelectronic implantable device. In this review, the modern fabrication methods of bioelectronic conduit for bridging critical nerve gaps after nerve injury are summarized, with regard to conductive materials and core manufacturing process. In addition, to deliver versatile electrical stimulation, the integration of implantable bioelectronic device is discussed, including wireless energy harvesters, actuators and sensors. Moreover, a comprehensive insight of beneficial mechanisms is presented, including up-to-date in vitro, in vivo and clinical evidence. By integrating conductive biomaterials, 3D engineering manufacturing process and bioelectronic platform to deliver versatile electroceuticals, the modern biofabrication enables comprehensive biomimetic therapies for neural tissue engineering and regeneration in the new era.